Tissue-Engineered Solutions in Plastic and Reconstructive Surgery: Principles and Practice - Al-Himdani, Sarah; Jessop, Zita M.; Al-Sabah, Ayesha; Combellack, Emman; Ibrahim, Amel; Doak, Shareen H.; Hart, Andrew M.; Archer, Charles W.; Thornton, Catherine A.; Whitaker, Iain S. (Frontiers in Surgery, 2017)
Recent advances in microsurgery, imaging and transplantation have led to significant refinements in autologous reconstructive options, however the morbidity of donor sites remains. This would be eliminated by successful clinical translation of tissue-engineered solutions into surgical practice. Plastic surgeons are uniquely placed to be intrinsically involved in the research and development of laboratory engineered tissues and their subsequent use. In this article we present an overview of the field of tissue engineering, with the practicing plastic surgeon in mind. The Medical Research Council (MRC) states that regenerative medicine and tissue engineering “holds the promise of revolutionising patient care in the twenty-first century”. The UK government highlighted regenerative medicine as one of the key eight great technologies in their industrial strategy worthy of significant investment. The long-term aim of successful biomanufacture to repair composite defects depends on interdisciplinary collaboration between cell biologists, material scientists, engineers and associated medical specialties, however currently there is a current lack of coordination in the field as a whole. Barriers to translation are deep rooted at the basic science level, manifested by a lack of consensus on the ideal cell source, scaffold, molecular cues and environment and manufacturing strategy. There is also insufficient understanding of the long-term safety and durability of tissue-engineered constructs. This review aims to highlight that individualised approaches to the field are not adequate and research collaboratives will be essential to bring together differing areas of expertise to expedite future clinical translation. The use of tissue engineering in reconstructive surgery would result in a paradigm shift but it is important to maintain realistic expectations. It is generally accepted that it takes 20–30 years from the start of basic science research to clinical utility, demonstrated by contemporary treatments such as bone marrow transplantation. Although great advances have been made in the tissue engineering field, we highlight the barriers that need to be overcome before we see the routine use of tissue engineered solutions.